In situ evaluation of high temperature stress in wheat (Triticum aestivum L.) - Validation of a portable heat trap chamber - Khomdram, Sushma; Barthakur, Sharmistha (Annals of Agricultural Research, 2016)
Terminal heat stress is emerging as a major threat to wheat crop since the beginning of this century with changes in climate condition. Here, to study the impact of heat stress in natura we designed an experiment by constructing a portable heat trap chamber and grew two wheat ideotypes WR544 and HD2967 in pots under normal and exposed to heat stress (4hr) at generative stages inside the heat chamber. The cultivar WR544 was also exposed to drought by water withholding for 15 days and exposed to high temperature within the chamber. Along with this, heat acclimatized seeds of both the varieties were also utilized for heat tolerant analyses. The portable heat trap chamber maintained ± 5°C differences in temperature from the ambient temperatures during the heat stress period. Gene expression profiling were carried out with two heat stress responsive genes, S-phase kinase associated protein 1-like protein (TaSKP1) and WRKY transcription factor (TaWRKY10) in flag leaf and post anthesis stages. Differential gene expression was seen for both the genes. Highest induction level of TaSKP1 was observed in acclimatized WR544 both in flag leaf and post anthesis.Whereas TaWRKY10 expression was maximum in combination of drought and heat stress exposed WR544 in both the stages. Taken together the results point out to the effectiveness of this heat trap chamber for evaluation of high temperature stress mechanism of wheat in field.